2016
DOI: 10.1177/0004867415617836
|View full text |Cite
|
Sign up to set email alerts
|

Key findings from the second Australian Child and Adolescent Survey of Mental Health and Wellbeing

Abstract: Mental disorders are common in children and adolescents, often have significant impact and are associated with substantial absences from school. Child and adolescent mental disorders remain an important public health problem in Australia. Accurate information about prevalence and severity of child and adolescent mental disorders is an essential prerequisite for effective mental health policy and service planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
660
11
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 500 publications
(719 citation statements)
references
References 33 publications
42
660
11
6
Order By: Relevance
“…This study used Young Minds Matter (YMM) data, a nationally representative survey of 6,310 Australians parent/carers of children and young people aged 4-17 years conducted between May 2013 and April 2014 [15,28]. The survey was designed to estimate national prevalence rates and associated burden of mental health disorders among children and young people.…”
Section: Participantsmentioning
confidence: 99%
“…This study used Young Minds Matter (YMM) data, a nationally representative survey of 6,310 Australians parent/carers of children and young people aged 4-17 years conducted between May 2013 and April 2014 [15,28]. The survey was designed to estimate national prevalence rates and associated burden of mental health disorders among children and young people.…”
Section: Participantsmentioning
confidence: 99%
“…The most recent large-scale epidemiological survey to be conducted in the UK found that one-in-ten (10 per cent) young people aged 5-16 years had been diagnosed with a mental disorder, one in five of whom experienced more than one disorder (Green et al, 2005). In Australia, one in seven (14 per cent) of those aged 4-17 years have been found to experience a 12-month mental disorder, 30 per cent of whom experience two or more disorders (Lawrence et al, 2015). Although neither the UK survey nor the Australian survey assessed for the presence of a substance use disorder, they did find higher rates of substance use among those with mental disorders.…”
Section: Christina Marel and Katherine L Millsmentioning
confidence: 90%
“…The importance of identifying, managing, and appropriately treating comorbidity in young people High rates of mental and substance use disorders have consistently been reported in national youth surveys conducted around the world (Ravens-Sieberer et al, 2008;Lawrence et al, 2015;Green et al, 2005;Kessler et al, 2012). Adolescence and young adulthood can be a difficult, turbulent time for many people, with an individual's thoughts, feelings, and behaviour affected by issues of change, development, identity formation, experimentation, rebellion, and uncertainty (Marsh et al, 2013).…”
Section: Christina Marel and Katherine L Millsmentioning
confidence: 99%
“…The draft ICD-11 also lists 'hazardous' gaming, referring to a pattern of use that increases the risk of harmful physical or mental health consequences, typically related to high frequency of use. There is a growing evidence base that links excessive gaming and Internet use to anxiety and depression (King, Delfabbro, Zwaans, & Kaptsis, 2013), physical health problems (Kelley & Gruber, 2012), school disconnection (Lawrence et al, 2015), decreased job productivity and unemployment (Young, 2010), and social isolation (Ceyhan & Ceyhan, 2008). Although the definitions of disordered and hazardous use vary across studies and regions, due to the use of different tools and guidelines for screen time, epidemiological studies to date have reported that young populations are particularly at risk of gaming and Internet-related problems, with prevalence rates of 'addictive' use at around 3% of users (Ferguson, Coulson, & Barnett, 2011) and rates of problem use as high as 8% (see King, Delfabbro, & Delfabbro, 2012).…”
Section: Introductionmentioning
confidence: 99%